PENGEMBANGAN GAGASAN AWAL UNTUK MENINGKATKAN SISTEM KETERAMPILAN MENULIS YANG BERJIWA - Maman A Majid Binfas; Nur Arafah; Hasmawati; Try Gustaf Said (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Writing skills are the ability to organize and develop highly complex logical ideas within a system, expressing critical and emotional thinking to produce meaningful written work. Writing skills are not only essential in academic settings but also across various professional and social fields. However, many people struggle to develop adequate writing skills. This can be attributed to various factors, such as a lack of understanding of how to write, difficulty in organizing ideas, and a lack of constructive feedback. While being a writer is indeed appealing, the moral responsibility in the afterlife must be taken seriously. This study aims to identify the development of ideas and effective strategies for improving writing skills so that they are meaningful. The methodology used is a historical study approach as part of a qualitative method with a descriptive model to obtain a realistic picture based on facts. Data collection was conducted through in-depth interviews with a blog writer who served as the research subject, and document analysis was performed to gather empirical data. The results of the study indicate that writing skills can be improved through several strategies, namely diligently reading various types of texts, writing regularly even in small amounts, and accepting feedback from others. These strategies can help develop ideas, understand writing structure, and boost motivation. With the application of appropriate conceptual strategies, writing skills can be significantly improved, resulting in informative and engaging works that embody the spirit of “mâ lâ yatimm al-wâjib illâ bihi fa huwa wâjib” (that which is necessary for the fulfillment of an obligation is itself an obligation) and serve as a mercy to all creation.